Quality of the water supply in public schools in the city of Humaitá, Amazonas, Brazil - Dos Santos, Mariano Vieira; Duarte, Miqueias Lima [UNESP]; da Silva, Tatiana Acácio [UNESP]; Valente, Keith Soares [UNESP]; de Oliveira, Hilma Margalhães (My University, 2019)
Water is an indispensable natural resource for life and human development and ensuring that this resource is of adequate quantity and quality should be a common objective for the authorities, since its contamination poses a major public health risk and causes a number of environmental problems. In this work, water potability conditions provided in two schools of the state public network of the city of Humaitá, located in south of the state of Amazonas, were evaluated. The water samples collected in schools were analyzed for physicochemical and biological parameters and compared to the reference values established by the Ministry of Health's Consolidation Ordinance n° 5/2017, which establishes the quality standards of water exclusively for human consumption. The results indicated the precarious conditions of the municipal public supply system; as a consequence, it has been observed that the water distributed for human consumption is not in compliance with the values established by the legislation and may cause health problems for the students who consume it. In this case, it is indicated that the disinfection of the water before consumption is carried out, in order to ensure quality and to meet the drinking standards.
Qualidade da água de abastecimento público em escolas da rede públicas no município de Humaitá, Amazonas, Brasil
Keywords: legislation; potability; schools; Water supply